Determinant of Digital Transformation on MSME Creative Industry: A Confirmatory Factor Analysis - Imam Darul Firmansyah; Herli, Mohammad; Ahmad Ghufrony (Ilomata International Journal of Management, 2025)
The latest study highlights the importance of the role of digital transformation in increasing the competitiveness of micro, small, and medium enterprises (MSMEs). However, the complex interaction between factors influencing digital adoption in MSMEs in the creative economy sector is still unresearched, especially in developing countries. This study aims to investigate the determinants of digital transformation adoption among MSMEs, focusing on the relative influence of organizational, technological, and environmental factors. We use a quantitative approach by conducting a survey of 254 MSME owners and managers. The data was analyzed using confirmatory factor analysis (CFA) to assess the relationship between variables. Our findings reveal that organizational factors exert the strongest influence on digital transformation adoption, followed by technology factors. Environmental factors, while significant, show a relatively lower impact. This study contributes to a more diverse understanding of digital transformation in MSMEs by emphasizing the excellence of the organization's internal capabilities. Our study shows that policies aimed at driving digital adoption should prioritize strengthening organizational readiness alongside technology support.